2010
DOI: 10.1038/labinvest.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Difference in expression of hepatic microRNAs miR-29c, miR-34a, miR-155, and miR-200b is associated with strain-specific susceptibility to dietary nonalcoholic steatohepatitis in mice

Abstract: The importance of dysregulation of microRNA (miRNA) expression in nonalcoholic steatohepatitis (NASH) has been increasingly recognized; however, the association between altered expression of miRNAs and pathophysiological features of NASH and whether or not there is a connection between susceptibility to NASH and altered expression of miRNAs are largely unknown. In the present study, male inbred C57BL/6J and DBA/2J mice were fed a lipogenic methyl-deficient diet that causes liver injury similar to human NASH, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 51 publications
(67 reference statements)
9
138
0
Order By: Relevance
“…2), indicating that the diet induced the characteristic steatosis pathology, mixed hepatic inflammatory and fibrosis, signifying a successful NASH model. (19) demonstrated that feeding C57BL/6J mice a methyl-deficient diet to induce NASH results in aberrant expression of miRNAs, including miR-122, miR-199a-5p and miR-221. To investigate the role of these three miRNAs in NASH, the levels of miR-122, miR-199a-5p and miR-221 were determined in the livers extracted from mice fed MCD and control diets, using RT-PCR experiments.…”
Section: Hepatic Inflammation and Fibrosis Following The MCD Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…2), indicating that the diet induced the characteristic steatosis pathology, mixed hepatic inflammatory and fibrosis, signifying a successful NASH model. (19) demonstrated that feeding C57BL/6J mice a methyl-deficient diet to induce NASH results in aberrant expression of miRNAs, including miR-122, miR-199a-5p and miR-221. To investigate the role of these three miRNAs in NASH, the levels of miR-122, miR-199a-5p and miR-221 were determined in the livers extracted from mice fed MCD and control diets, using RT-PCR experiments.…”
Section: Hepatic Inflammation and Fibrosis Following The MCD Dietmentioning
confidence: 99%
“…Alterations in the expression levels of miR-29c, miR-34a, miR-155 and miR-200b, hepatic miRNAs, were associated with differences in the pathophysiological and pathomorphological features of NASH (19). Furthermore, in a study screening for altered expression levels of hepatic miRNAs associated with NASH, a total of 23 miRNAs were reported to be underexpressed or overexpressed in NASH, with the predicted targets of these miRNAs known to affect cell proliferation, metabolism, protein translation, apoptosis, inflammation and oxidative stress (20).…”
Section: Introductionmentioning
confidence: 99%
“…, Sun et al (23) Diallyl disulfide (garlic) Histone modifications Cancer prevention Ficz et al (15) , Delage & Dashwood (16) High-cholesterol diet MicroRNAs Obesity Pogribny et al (26) High-fat diet DNA methylation Obesity; metabolic syndrome Buckley et al (45) , Khan et al (46,47) Dietary methyl deficiency MicroRNAs Non-alcoholic steatohepatitis; liver cancer…”
Section: Effects Of Nutritional Factors On Dna Methylationmentioning
confidence: 99%
“…14,36 Notably, miR-34a has been shown to be up-regulated in both human serum 50,51 and liver in humans and animal models of NAFLD. 14,55,121,122 Two recent studies suggest two differing mechanisms for the involvement of miR-34a in NASH pathogenesis through down-regulation of SIRT-1; a) leading to AMP kinase dephosphorylation and subsequent decreased phosphorylation of HMGCoA, ultimately leading to cholesterol accumulation 121 ; b) increased acetylation of p53 causing activation of apoptosis. 123 MiR-122 is significantly down-regulated in humans and animal models of NAFLD patients.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%